Improving Newborn Care Knowledge and Practices through Training for Mothers and Posyandu Cadres in Rural Areas - Sirajul Muna; Yayuk Sri Rahayu; Wibowo Hanafi Ari Susanto (CV. Get Press Indonesia, 2025)
Background. Inappropriate newborn care practices (NBW) contribute significantly to neonatal morbidity and mortality. This study aims to evaluate the effectiveness of training in improving knowledge and practice of newborn care among mothers and Posyandu cadres in rural areas. Methods. A quasi-experimental design with a pre-test and post-test approach without a control group was used. Data were collected through structured questionnaires and observation sheets, which had been validated by experts and tested for reliability before use. Results. The results of the study indicate that a two-day intensive training has proven effective in improving mothers' and cadres' knowledge and practices regarding newborn care. The training, which was designed interactively and applicatively, was able to encourage significant improvements, especially in the aspects of Kangaroo Mother Care (KMC) and the ability to recognize neonathal danger signs. Conclusion. The findings suggest that simple yet structured interventions can be a potential strategy in supporting efforts to reduce newborn mortality in areas with limited access to professional health services.